Nafs al-Lawwāmah as a Moral-Spiritual Awareness Framework in Islamic Religious Education - Gigih Hadi Nugroho Said; Rahman Zaki Rizaldy; Yusuf Qardhawi Ridho Sarky; Fajar Ardyansah; Suhartono (Yayasan Azhar Amanaa Yogyakarta, 2026)
This This study aims to construct the Nafs al-Lawwāmah Moral-Spiritual Awareness Model as a conceptual framework for strengthening moral-spiritual awareness in Islamic Religious Education. The study employed an integrative qualitative conceptual design supported by empirical evidence collected from 25 undergraduate students of the Islamic Religious Education program selected through purposive sampling. Primary data were derived from the thematic interpretation of Qur'an 75:2 and Tafsir Ibn Kathir, while secondary data were obtained from contemporary literature on Islamic Religious Education, Islamic psychology, and moral psychology. Empirical data were collected using an online questionnaire consisting of Likert-scale items and open-ended questions, then analyzed through thematic content analysis, thematic synthesis, descriptive statistics, thematic coding, and conceptual mapping. The findings identified five interconnected dimensions of moral-spiritual awareness, namely spiritual guilt, self-reflection (muhasabah), repentance (tawbah), accountability before Allah, and behavioural improvement. Qualitative analysis further revealed six overarching themes that explain how students interpret moral awareness as a dynamic process of spiritual transformation. Based on the integration of Qur'anic interpretation, literature synthesis, and empirical findings, this study proposes the Nafs al-Lawwāmah Moral-Spiritual Awareness Model, which repositions nafs al-lawwāmah from a theological concept into a pedagogical framework for Islamic Religious Education. The proposed model contributes to the development of reflective and transformative learning by integrating spiritual awareness, self-regulation, repentance, and transcendental accountability into a coherent educational framework.